2015 Applications and Innovations in Mobile Computing (AIMoC) 2015
DOI: 10.1109/aimoc.2015.7083828
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-based comb-needle model for energy-efficient data aggregation in wireless sensor networks

Abstract: This paper deals with information discovery and aggregation in large scale wireless sensor networks applied for mission-critical applications like military reconnaissance. To support query processing based on the gathered information, an efficient and reliable information discovery mechanism is proposed for sensor networks. We extend the basic Comb-Needle Discovery Support Model [3] by including Cluster-based data aggregation mechanism, which helps minimize the communication cost. Clusterbased approach groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In CH level, use three methods of distance functions, one-way ANOVA model, and set similarity function. The authors [ 18 ] have proposed a cluster-based data aggregation approach using the Comb-Needle model, which aims to minimize communication cost and energy consumption. The authors [ 19 ] have proposed a clustering approach in Underwater Sensor Network (UWSN) based on aggregation with Euclidean distance, aiming at data redundancy and analyzing network throughput and energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…In CH level, use three methods of distance functions, one-way ANOVA model, and set similarity function. The authors [ 18 ] have proposed a cluster-based data aggregation approach using the Comb-Needle model, which aims to minimize communication cost and energy consumption. The authors [ 19 ] have proposed a clustering approach in Underwater Sensor Network (UWSN) based on aggregation with Euclidean distance, aiming at data redundancy and analyzing network throughput and energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers' interest in designing data aggregating techniques has grown rapidly in past few years (Al-Karaki et al 2004;Nandini and Patil 2010;Dagar and Mahajan 2013;Randhawa and Jain 2017;Dhand and Tyagi 2016;Gherbi 2015;Fang et al 2019;Shanmukhi and Ramanaiah 2015). In Al-Karaki et al (2004), author presented exact algorithms and approximate algorithms to select optimal number of aggregation points in the network.…”
Section: Data Aggregationmentioning
confidence: 99%
“…In addition, this scheme not only minimizes communication overhead and energy utilization meanwhile it also preserves privacy in data communication. A comb needle discovery model for query processing is extended by introducing a cluster-based data combining method into it (Shanmukhi and Ramanaiah 2015). This extension results in minimizing the communication cost and energy utilization of the network, thereby enhancing the network life duration.…”
Section: Data Aggregationmentioning
confidence: 99%
“…X. Liu [32] proposed Comb Needle Model to perform data aggregation based on push and pull strategies. Shanmukhi et al [33] had demonstrated Cluster based Comb Needle Model for grid networks. It has minimized communication cost and maximized the throughput.…”
Section: Existing Work On Data Aggregation In Wsnmentioning
confidence: 99%
“…Clustering has been added to CNM for regular network [33] to perform efficient data aggregation with energy efficiency. The basic CNM is extended to support the data aggregation in randomly deployed sensor networks [17] as shown in Figure 2.…”
Section: Proposed Conceptmentioning
confidence: 99%